PENGGUNAAN PENJAMINAN BUY BACK GUARANTIE OLEH DEVELOPER TERHADAP KREDIT PEMILIKAN RUMAH (STUDI KASUS DI BANK BUKOPIN CABANG MEDAN) - MOCHAMMAD ERWIN RADITYO (PREMISE LAW JURNAL, 2015)
Nowdays, with increased competition in terms of the housing business, the Bank has made ​​developers with a buy-back agreement with guarantie. In guarantie buy back agreement between the Bank and the developer included a promise from the developer to buy back the collateral if the loan facility granted by the Bank to the debtor of bad loans occurred. Position and buy back guarantee guarantie role in buying and selling residential units with a mortgage facility is a developer will buy the land and buildings that have been sold in the case of negligent debtors, other than that the guarantor will help the bank to get a bank / control of land and buildings, the developer guarantees made will apply continuously and lasted until the debtor to the bank debt has been paid in full. Form of legal relationship of the parties in the fulfillment of the obligations guaranteed buy back guarantie is the relationship between the Bank and the debtor set forth in the credit agreement, while the banks of the agreement with the developer to buy back guarantie, then the developer with the debtor is a legal relationship arising through subrogation institutions. Regarding the realization of guaranteed buy back guarantie, bank / creditor has two (2) alternatives to complete and return rights, namely the Bank exercising its rights under the agreement made ​​by the debtor, or exercising its rights under the agreement to buy back guarantie. Keywords: Buy Back Guarantee, Housing Credit